Versatile applications of three-dimensional objects fabricated by two-photon-initiated polymerization. (14th November 2018) - Ha, Cheol Woo; Prabhakaran, Prem; Lee, Kwang-Sup
Abstract: Abstract : In this topical review of two-photon stereolithography (TPS), we discuss novel materials and demonstrate applications of this technology. Two-photon-initiated chemical processes are used to fabricate arbitrary three-dimensional structures in TPS. In the first part of this article, the development of novel photoactive materials to fabricate pure inorganic or organic–inorganic hybrid microstructures is discussed. The second part discusses the fabrication of functional microstructures for highly specific applications to demonstrate the importance of TPS in different fields of science.